The Enigma of Terrence Malick's Days of Heaven: History, Nature, and Utopia in the American West. - Cottle, Stuart (Quarterly Review of Film & Video)
The article reports that basic narrative framework yields a number of cinematic opportunities for Terrence Malick. Topics include considered that by situating his narrative in 1916, Malick is able to survey, through the eyes of this trio of naïve protagonists, something of the social and political tumult of the "Progressive Era."